SEMPER I: a novel semi-empirical model for the radio emission of star-forming galaxies at 0 < z < 5 - Giulietti, Marika; Prandoni, I.; Bonato, M.; Bisigello, L.; Bondi, M.; Gandolfi, G.; Massardi, M.; Boco, Lumen; Rottgering, H. J. A.; Lapi, A. (Astronomy and astrophysics, 2025)
Context. Star-forming galaxies (SFGs) are the dominant population in the faint radio sky, corresponding to ﬂux densities at 1.4 GHz < 0.1 mJy. A panchromatic approach is essential for selecting SFGs in the radio band and understanding star formation processes over cosmic time. Semi-empirical models are valuable tools to eﬀectively study galaxy formation and evolution, relying on minimal assumptions and exploiting empirical relations between galaxy properties and enabling us to take full advantage of the recent progress in radio and optical/near-infrared (NIR) observations.